Análise dos termos utilizados na consulta de enfermagem no pré-natal com base na classificação internacional para a prática de enfermagem - Souza, Eni do Carmo de (2012)
The objective of the present work was to analyze the terms used during nurse consultations in the prenatal period, based on the International Classification for Nursing Practice -CIPE® version 2011. It is a cross-sectional exploratory study, carried out between the months of April and May 2012, at 15 Basic Health Units in the city of Londrina-PR. The study analyzed the notes of 269 hospital records from pregnant women who were in the 3rd quarter of gestation and had at least one pre-natal consultation with a nurse. These records revealed 557 nursing consultations, which resulted in the transcription of 25,189 terms. From those, were excluded medical diagnoses without recommended conducts for nurses in either local or nationwide protocols, pseudo-terminological terms, numbers, names of services, cities or medications, which were organized in pharmacological classes, resulting in a total of 1,761 terms. Using cross-mapping, which is a technique used to compare data with possible similarity, 311 constant and 1,451 not-constant terms were identified. Those terms were given their respective theoretical definitions according to CIPE® 2011, as: identical, similar, more comprehensive, more restricted or without concordance. Thus, for the constant terms, 95 (30.6%) terms were classified as identical to the ones in CIPE®; 61 (19.6%) were more comprehensive than the ones used in CIPE®; 148 (47.8%) were more restricted; 4 (1.3%) were similar to the ones used in CIPE®; and 3 (1.0%) were not classified. Of the non-constant terms, 202 (13.9%) were similar, and 1.451 (86.1%) were regarded as non-concordant. The great percentage of constant terms classified as more restricted (47.8%), may indicate the need for the International Council of Nurses (ICN) to improve these definitions. For non-constant terms, the 86.1% rate of non-concordance indicates the use of great variability of terms by these professionals which may compromise biological, psychological, social and spiritual aspects of human life. It reveals the use of non-standardized terms by those nurses, can interfere with the continuity and integrality of care rendered to pregnant women. Among the recommendations, there is the validation of the terms with their respective theoretical definitions to nurses of Basic Health Unit that create or use such vocabulary. It is believed that the results of the present study may contribute to expand the discussion on the importance of a Systematization of Nursing Care in Prenatal units, as well as to promote the creation of a Prenatal Nursing Language Term Database to eventually aid in describing the elements of their practice (diagnosis, intervention and results) for obstetric care in basic healthcare.